Failure characteristic of class 1E electrical cable used in the nuclear power plant exposed to fire. (August 2022) - Zhao, Hongru; Tong, Jiejuan; Zhao, Jun; Wu, Jing
Abstract: The failure analysis of electrical cable plays important role in Fire Probabilistic Risk Assessment (PRA) of nuclear power plant (NPP). This work is to present an experimental study of the failure characteristics of Class 1 E electrical cables in different fire exposure conditions and raceway configuration. The results show that power cable has relatively higher failure temperature and longer failure time than control cable. For cables in Tray-type configuration or Conduit-type configuration, the failure temperature in persistent flame zone and intermittent flame zone are similar, but are quite different from that in hot gas layer. While for the cables in Air Drop-type configuration, TA-PF > TA-IF > TA-HG is presented. Given the same fire exposure conditions, the failure patterns of cables in Tray-type configuration and in Conduit-type configuration are similar in terms of time and temperature, but are quite different from that in Air drop-type configuration. Highlights: The power cable has relatively higher failure temperature and longer failure time than control cable. The failure temperature of cables in flame zone are different from that in hot gas layer. The failure patterns of cables in different raceway configurations show some significant differences.